Development, analysis and assessment of a fuel cell and solar photovoltaic system powered vehicle - Ezzat, M. F.; Dincer, I. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This paper deals with a new hybridly powered photovoltaic-fuel cell- Li-ion battery integrated system and is compared to a base system, consisting of PEM fuel cell and Li-ion battery. It investigates the effects of adding photovoltaic arrays to the base system and further effects on the overall energy and exergy efficiencies and hence hydrogen consumption. These two systems are analyzed and assessed both energetically and exergetically. The study results show that the overall energy and exergy efficiencies become 39.46% and 56.3%, respectively at a current density of 1150 mA/cm(2) for system 1 (fuel cell-battery). Moreover, energy and exergy efficiencies are found to be 39.86% and 56.63% at current density of 1150 mA/cm(2) for system 2 (fuel cell-battery-photovoltaics). Utilizing photovoltaic arrays in system 2 would recover 561 g of hydrogen through 3 h of continuous driving at max power of 98.32 kW, which is approximately 11.2% of the hydrogen storage tank used in the proposed systems. The effects of changing various system parameters on energy and exergy efficiencies of the overall system are also examined. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Photovoltaics; Fuel cell; Integrated system; Energy; Exergy; Efficiency; PERFORMANCE; Thermodynamics; Energy & Fuels; Mechanics